In Vitro Antiplasmodial Activity and Cytotoxicity of Isolates of Pasak Bumi (Eurycoma longifolia Jack) Root - Eti Nurwening Sholikhah; Mahardika Agus Wijayanti; Laela Hayu Nurani; Mustofa Mustofa (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Previous study showed that methanol soluble fractions of Eurycoma longifolia Jack showed a high in vitro antiplasmodial activity, however there is no explanation which isolate is active as antiplasmodial. This study was conducted to evaluate the in vitro antiplasmodial activity and cytotoxicity of 5 isolates of E. longifolia root isolated from methanol soluble fractions. The in vitro antiplasmodial activity was tested on two strains of P. falciparum, FCR-3 and D10 while their cytotoxicity was tested on normal Vero cell line. The antiplasmodial activity and the cytotoxicity were presented as the Inhibitory Concentration 50% (IC50) which showed the concentration of isolate which inhibit the Plasmodium or Vero cell line growth 50%. The IC50 value was determined by probit analysis. The selectivity of isolate was determined by calculating the ratio of the cytotoxicity (IC50 on Vero cell line) with the antiplasmodial activity (IC50 on Plasmodium). The results showed that isolate 4 and 5 showed high antiplasmodial activity with IC50 value 2.21-19.02, 13.54-64.73 µg/mL respectively. The cytotoxic/antiplasmodial ratio indicates that isolate 4 and 5 have also high selectivity with value 11.74-68.75 for isolate 4, and 66.01-316.51 for isolate 5. For conclusion, the isolate 4 and 4 showed the high aniplasmodial activity with the high selectivity